2001
DOI: 10.1080/10903120190940416
|View full text |Cite
|
Sign up to set email alerts
|

S Pinal I Mmobilization in the F Ield : C Linical C Learance C Riteria and I Mplementation

Abstract: Awareness of the health and financial repercussions of unnecessary immobilization has made cervical spinal immobilization controversial in out-of-hospital care. Clinical criteria for clearance of the cervical spine in the hospital based on mechanism of injury have been supported by many trauma centers. However, implementation of clinical criteria for cervical spinal clearance in out-of-hospital settings is not as well validated by multicenter studies or accepted by many emergency departments. This consensus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…This practice is based on the assumption that immobilisation minimises spinal movement [14,15], reduces risk of secondary injuries [15,16], and facilitates extrication and transport [15]. There is emerging evidence, however, that spinal immobilisation may be associated with adverse effects, including increased risk of respiratory compromise [15,17,18], back and neck pain [17][18][19][20][21], pressure sores [22,23], and increased intracranial pressure [24]. Moreover, it may lead to additional cost and scene time [17], as well as the possible risk of dropping the immobilised patient by prehospital providers in difficult extrication situations when traversing narrow and unstable paths [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…This practice is based on the assumption that immobilisation minimises spinal movement [14,15], reduces risk of secondary injuries [15,16], and facilitates extrication and transport [15]. There is emerging evidence, however, that spinal immobilisation may be associated with adverse effects, including increased risk of respiratory compromise [15,17,18], back and neck pain [17][18][19][20][21], pressure sores [22,23], and increased intracranial pressure [24]. Moreover, it may lead to additional cost and scene time [17], as well as the possible risk of dropping the immobilised patient by prehospital providers in difficult extrication situations when traversing narrow and unstable paths [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…208 Altogether, there is a wide range of algorithms based on different clinical criteria for clearance of the cervical spine in the prehospital setting. [87][88][89][90][91]205,[208][209][210][211][212][213][214][215][216][217][218] Patients with reduced consciousness Patients with reduced consciousness have a higher prevalence of CSIs, and cervical spine clearance in such patients is not as clear cut as in conscious patients.…”
mentioning
confidence: 99%
“…These workers prospectively showed that these criteria were not affected by mechanism of injury, missing 3% and 6% of injuries in high and low risk groups, respectively [93]. These two studies prompted the production of practice guidelines for selectively immobilizing trauma victims during transfer [94,95], and clinical criteria identified 280 ⁄ 295 (94.9%) of cervical injuries [33]. Available evidence suggests that applying prehospital clinical criteria may raise suspicion of approximately 90% of spinal injuries but has little capacity to identify individual cases, and carries an unacceptable false negative rate of 10%.…”
mentioning
confidence: 99%